Some Correlates of Marriage among the Population of the Central Part of Kosovo and Metohija - Minić, Jelena Lj.; Jaredić, Biljana N.; Kolić, Suzana D. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The subject of the study was to examine the quality of a marriage correlates in population in Kosovo and Metohija. The main goal of the research was to examine the relationship of marriage quality with: marital locus of control, social support, length of marriage, age, material status and educational level of the respondents. The sample was consisted of respondents of both sexes (N = 200) with a permanent residence in the central part of Kosovo and Metohija. The study used: scale of adaptation in marriage, scale of marital locus control, evaluation list of interpersonal support and the questionnaire of the elementary data of the respondents. The data were analyzed by descriptive statistics, correlation analysis and by t-test. The results showed that the quality of marriage and individual dimensions are: satisfaction of marriage, cohesion, couple’s harmony and expressing emotions are closer to theoretical maximum. Marital locus of control is low in regard to the theoretical maximum, while the external marital locus of control is average value. Social support expressed in general, as well as individually by the perception of availability, (ie. The type of perceived social support: evaluation as (informative) support, touchable (concrete) support, self-esteem and belonging to support to support) is closer to the theoretical maximum. There is negative correlation between internal locus of control with the quality of marriage in general and in dimensions (marriage satisfaction, cohesion and couple’s harmony). Then negative correlation of internal locus of control with age and years spent in marriage and positive correlation of internal locus of control with material status and self-esteem as a type of perceived social support. There was not obtained statistically significant correlation quality of marriage with external marital locus of control. There were not obtained statistically significant correlation of age, years spent in marriage, material status and educational level of respondents with social support in general and by type observed social support. By these studies the different results were obtained than supposed ones, which indicate to certain specifics of a sample, but also selection of respondent that could affect the results. The obtained results showed that the study of this issue should continue, with the involvement of a larger number of respondents and other variables, which are supposed that are associated with the quality of marriage, but not covered by this study. It is particularly important to continue the research correlates of the quality of marriage, spouses and families in whole on the sample in Kosovo and Metohija, because it is the sample and the issue that almost were not researched in this area.